Muslim friendly hospitality services: an overview of Muslim friendly hotel services concept in Malaysia - Mohd Daud, Noor Najihah; Abas, Afridah (Kulliyyah of Languages and Management (KLM), International Islamic University Malaysia (IIUM), 2016)
Muslim friendly hospitality services (MFHS) in Malaysia has recorded a well progressive records and accolade in myriad achievements according the latest report, 2015 released by Thomson Reuters. Being one of the supply drivers for the travel industry, it is undoubted that this MFHS is significant to be examined in order to ensure its sustainability and most importantly to cater Muslim guest needs. The vibrancy of this development witnessing a variety of MFHS have been introduced and customized. However, it was discovered that, the concept and understanding on MFHS in Malaysia are still not clear and vague. In fact, the discussion in academic literature pertaining on the concept of MFHS is scanty. Therefore, this conceptual paper will be discussed on the existing concept of MFHS in Malaysia by delimiting into one of its sectors which is Muslim-friendly hotel industry by looking into their operational and facilities aspects in terms of its practices, complemented with managerial perspectives for its guidelines. This research will be conducted by using qualitative approach, using content analysis and observation. At the end of the discussion, this research will discuss and highlight on the practices of Muslim friendly hotel services according to the newly-established standards, known as Malaysian Standard, MS2610:2015 Muslim friendly Hospitality Services-Requirements. This guideline will become a main source of reference for the authority bodies, industry players as well as hoteliers in implementing this concept into their business. Hopefully in the future, this research will be beneficial to the researchers, academicians, industry players, as well as consumer as a whole.